Evaluación de la presencia de Aflatoxinas (B1, B2, G1, G2) en alimentos balanceados para caninos comercializados a granel en establecimientos de Chía, Cundinamarca (2021)
The present research work was carried out in order to make an evaluation of the presence of aflatoxins (B1, B2, G1, G2) in balanced food for dogs marketed in bulk in establishments in the municipality of Chia Cundinamarca, in relation to the problem that It exists due to the contamination of food and raw materials used for the production of concentrate for canines by the fungus Aspergillus flavus, which is a ubiquitous microorganism, having the ability to thrive in water, soil and air, colonizing harvest crops along its path , transport vehicles and continue their dissemination and growth under optimal storage conditions for these products.